Subtype-Specific Surface Proteins on Adipose Tissue Macrophages and Their Association to Obesity-Induced Insulin Resistance - Strand, Kristina; Stiglund, Natalie; Haugstøyl, Martha Eimstad; Kamyab, Zahra; Langhelle, Victoria; Lawrence-Archer, Laurence; Busch, Christian; Cornillet, Martin; Hjellestad, Iren Drange; Nielsen, Hans Jørgen; Njølstad, Pål Rasmus; Mellgren, Gunnar; et al. (Frontiers in Endocrinology, 2022)
A chronic low-grade inflammation, origniating in the adipose tissue, is considered a driver of obesity-associated insulin resistance. Macrophage composition in white adipose tissue is believed to contribute to the pathogenesis of metabolic diseases, but a detailed characterization of pro- and anti-inflammatory adipose tissue macrophages (ATMs) in human obesity and how they are distributed in visceral- and subcutaneous adipose depots is lacking. In this study, we performed a surface proteome screening of pro- and anti-inflammatory ATMs in both subcutaneous- (SAT) and visceral adipose tissue (VAT) and evaluated their relationship with systemic insulin resistance. From the proteomics screen we found novel surface proteins specific to M1-like- and M2-like macrophages, and we identified depot-specific immunophenotypes in SAT and VAT. Furthermore, we found that insulin resistance, assessed by HOMA-IR, was positively associated with a relative increase in pro-inflammatory M1-like macrophages in both SAT and VAT.